Improving Problem Solving Skill and Self Regulated Learning of Senior High School Students through Scientific Approach using Quantum Learning strategy - M Sudirman; S Fatimah; A Jupri (Universitas Sebelas Maret, 2017)
This research is quasi experiment with control group pretest-postest design. The sampel in this research using the techique of purposive sampling so the samples used were two classes of the 11th grade students of SMAN 14 Bandung in the academic year 2017/2018. The experiment group uses saintific approach using Quantum Learning strategy and control group uses saintific approach. In collecting the data the researcher will use the test of problem solving ability and self regulated learning as the instrument. The aims of this research are to:1)find out the improvement of students mathematical problem solving through scientific approach using Quantum Learning study, 2) find out students self regulated learning through scientific approach using Quantum Learning.